War, Crisis and Sovereign Loans: The Greek War of Independence and British Economic Expansion in the 1820s - Chatziioannou, Maria Christina (The Historical Review/La Revue Historique, 2013)
This article focuses on the principal actors who undertook the financial intermediation of the Greek loans of 1824 and 1825 and the agents who carried it out, the financial market, the stock market exchange and the joint-stock corporate organization. The main argument is that there was an asymmetric relationship between these principal actors and agents. My research hypothesis works on the convergence of two different crises at the same time: the systemic banking crisis of 1825 in London; and the severe internal crisis for the insurgent Greeks. I argue that the causes for these “hapless loans” could be more complex, beyond the known moral critique.